Interactions of productivity, content of separate amino acids, general protein in blood serum of chickens and tone of the autonomic nervous system - A. A. Studenok; E. O. Shnurenko; V. I. Karpovskyi; O. V. Zhurenko; D. I. Kryvoruchko; B. V. Gutyj; V. O. Trokoz (Regulatory Mechanisms in Biosystems, 2021)
The regulation of metabolic processes and maintenance of a stable internal environment of the body is the role of the autonomic nervous system (ANS). It influences all systems and organs, thus along with the neuro-humoral system providing control over the metabolism of proteins, fats and carbohydrates. Amino acids, as structural units of any protein molecule, are essential for the metabolism of proteins, enzymes and hormones. Certain amino acids are involved in neutralizing free radicals and are a donor of metal groups, can act as an energy source in case of a deficiency of carbohydrates and fats, and be structural units of connective tissue. Exchange of these compounds and their regulation by ANS have not been studied sufficiently, therefore, it is necessary to carry out research in this direction. The studies were aimed at finding the presence of the regulatory effect of ANS on the content of individual amino acids in the blood serum of 60-day-old Cobb-500 chickens. Determination of the ANS tone in Cobb-500 chickens at the age of 30–35 days was determined by the method of variation pulsometry. Electrocardiographic examination was performed in a quiet room without the use of sedatives. At the age of 60 days, blood was obtained from the saphenous vein of the chickens’ shoulder. Blood was sampled from 10 am to 1 pm, after a short fasting (2:00). It was found that sympathicotonic chickens had a higher content of individual amino acids compared to normotonics and vagotonics. In vagotonic chickens, the content of glycine and serine in the blood serum significantly exceeded the rate of chickens with a balanced tone of ANS. Correlative relationships between amino acid content were highly significant in poultry with balanced ANS tone. Vagotonic chickens had the highest correlations between ANS tone, heart rate and amino acid content (trend). Correlative relationships were present between ANS and body weight of chickens of different groups, serum protein. The correlation between total serum protein and body weight of chickens was different depending on the tone of the ANS. Fisher’s test revealed a significant effect of balanced ANS tone on the content of valine, serine and glycine and the weight of chickens. The effect of ANS tone on weight in vagotonic birds was high.